Durabilidade de fibrocimento reforçado com polpa de sisal após 10 anos de envelhecimento natural - Farrapo, Camila Laís (2015)
Cementitious materials are typically characterized by their brittle trait. Thus, the insertion of fibers as reinforcement improves the composite’s energy absorption. The conventional material used as reinforcement for fiber cement is asbestos. However, global tendency is to review the use of this mineral fiber. The use of natural fibers as reinforcement in fiber cement generates high expectations, but the durability of this type of composite is still a challenge. Thus, this work aimed at assessing the effect of several techniques (addition of synthetic fibers, carbonation and autoclaving) to increase the durability of reinforced roofing tiles with sisal pulp. The roofing tiles were produced by means of vacuum-pressure process, used to evaluate the percentage of sisal pulp in association or not with polypropylene fibers, as well as the effect of carbonation and autoclaving over the durability of cement composites. The natural aging of the roofing tiles was done over a 10-year period, in the municipality of Pirassununga, São Paulo, Brazil. We evaluated physical, mechanical and microstructural properties after such period, and compared the results to those obtained after 28 days. After aging, the higher polypropylene contents was, the best was the performance of the tiles, given that, unlike natural fibers, synthetic fibers do not degrade the cement over time. Regarding the carbonation, even after aging, the technique allowed the partial preservation of plant fiber in an alkaline environment, fact confirmed in the mechanical results with images obtained by means of scanning electron microscopy and X-ray diffraction. After 28 days, the autoclaved tiles presented the worse outcomes when compared to non-autoclaved. However, after 10 years, autoclaving was efficient and aided in preserving the plant material in the cement matrix.